Constrained Pseudo-Market Equilibrium - Echenique, Federico; Miralles, Antonio; Zhang, Jun (American Economic Review, 2021)
We propose a pseudo-market solution to resource allocation problems subject to constraints. Our treatment of constraints is general: including bihierarchical constraints due to considerations of diversity in school choice, or scheduling in course allocation; and other forms of constraints needed to model, for example, the market for roommates, combinatorial assignment problems, and knapsack constraints. Constraints give rise to pecuniary externalities, which are internalized via prices. Agents pay to the extent that their purchases affect the value the of relevant constraints at equilibrium prices. The result is a constrained-efficient market-equilibrium outcome. The outcome is fair to the extent that constraints treat agents symmetrically. (JEL D47, D61, D63, I11, I21)